(4 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
We are given the input to an LTI system along with the system's impulse response and told to find the output y(t).  Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.
 
We are given the input to an LTI system along with the system's impulse response and told to find the output y(t).  Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.
  
  <math>y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(t-\tau)x(t)d\tau</math>
+
  <math>y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(t-\tau)x(t)d\tau</math> ('''''COMMUTATIVE PROPERTY''''')
  
  
Line 8: Line 8:
 
<math>
 
<math>
 
\begin{align}
 
\begin{align}
  y(t) & = \int_{-\infty}^\infty e^{-t-\tau}u(t-\tau)u(\tau-1)d\tau \\
+
  y(t) & = \int_{-\infty}^\infty e^{-(t-\tau)}u(t-\tau)u(\tau-1)d\tau \\
       & = \int_1^\infty e^{-t-\tau}u(t-\tau)d\tau \\
+
       & = \int_1^\infty e^{-(t-\tau)}u(t-\tau)d\tau \\
       & = \int_1^{t} e^{-t-\tau}d\tau  \\  
+
       & = \int_1^{t} e^{-(t-\tau)}d\tau  \\  
 
       & = e^{-t}\int_1^{t} e^{\tau}d\tau  \\  
 
       & = e^{-t}\int_1^{t} e^{\tau}d\tau  \\  
 
       & = e^{-t}(e^{t} - e) \\
 
       & = e^{-t}(e^{t} - e) \\

Latest revision as of 16:56, 30 June 2008

We are given the input to an LTI system along with the system's impulse response and told to find the output y(t). Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.

$ y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(t-\tau)x(t)d\tau $  (COMMUTATIVE PROPERTY)


Plugging in the given x(t) and h(t) values results in:

$ \begin{align} y(t) & = \int_{-\infty}^\infty e^{-(t-\tau)}u(t-\tau)u(\tau-1)d\tau \\ & = \int_1^\infty e^{-(t-\tau)}u(t-\tau)d\tau \\ & = \int_1^{t} e^{-(t-\tau)}d\tau \\ & = e^{-t}\int_1^{t} e^{\tau}d\tau \\ & = e^{-t}(e^{t} - e) \\ & = 1-e^{-(t-1)}\, \mbox{ for } t > 1 \end{align} $


Since x(t) = 0 when t < 1:

$ y(t) = 0\, \mbox{ for } t < 1 $


$ \therefore y(t) = \begin{cases} 1-e^{-(t-1)}, & \mbox{if }t\mbox{ is} > 1 \\ 0, & \mbox{if }t\mbox{ is} < 1 \end{cases} $

Alumni Liaison

Have a piece of advice for Purdue students? Share it through Rhea!

Alumni Liaison